Philosophy & Aesthetics of Kendang in The Sundanese Concept of Life - Rizali, Rizki; Budiman, Agus; Sukmayadi, Yudi (Universitas Negeri Medan, 2023)
The characteristics of Sundanese kendang in a review of multiple cultural perspectives are sufficient to provide space for exploration in the process of acculturation of traditional arts at national and international levels. Sundanese kendang has shown its existence as a collaborative local cultural product. However, the acculturation of Sundanese kendang which is currently growing has certain problems on the other hand. Through the various charms it offers, Sundanese kendang are now not only owned by the Sundanese people, but are already owned by other non-Sundanese people. Therefore, of the many changes in the process of development and distribution, identification of how the Sundanese kendang looks today is quite important to complement the Sundanese kendang literacy itself as a complete identity. Sundanese kendang as a cultural product are certainly inseparable from the Sundanese people as their owners. Periodically, Sundanese kendang have not found common ground about when, where, and who can be used as an accurate reference source for the interests of Sundanese kendang literacy itself, therefore this paper offers an approach through the pattern of rationality of Sundanese culture which allows it to be used as an option. in the study of Sundanese kendang as one of the cultural products of the Sundanese people. The philosophy of the Sundanese people will be reflected in the meaning contained in the Sundanese kendang as one of the cultural products it produces. By discovering the cultural values contained in Sundanese kendang, it will provide a new view of what, why and what is wrong with Sundanese kendang.